Evaluation of prognostic indicators for canine primary immune‐mediated haemolytic anaemia and application of a scoring system for the determination of prognosis. Issue 4 (April 2015) - Ke, SS; Anderson, GA; Connolly, SL
Abstract : Objective: Apply a previously described scoring system retrospectively to cases of canine primary immune‐mediated haemolytic anaemia (pIMHA) to determine its accuracy and reliability for the determination of prognosis in Victoria, Australia. Methods: Retrospective cohort study of 41 dogs diagnosed with pIMHA at the University of Melbourne Veterinary Hospital (UMVH) between August 2006 to December 2012. Results: Of the 41 dogs included, 70.7% were female while 29.3% were male. The overall mortality in this study was 43.9%. The previously described prognostic scoring system when applied to cases of pIMHA in Victoria, Australia, was not found to show statistical significance for prognostification. None of the five prognostic factors were found to be independently significant for prognostification. Conclusion: Application of the previously described prognostic scoring system indicated that it may not be reliable for predicting prognoses of dogs with pIMHA in Victoria, Australia.